DAKWAH PRA KENABIAN: Reorientasi Dakwah melalui Pendekatan Historis - Haidir Rahman (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Nowadays, dakwah is perceived merely as a process of communicating Islamic teachings. If we take a closer look into the life of the Prophet Muhammad, we can safely assume that dakwah is more than just a process of communicating Islamic teachings from some person to others. Prophet Muhammad dedicated most of his life preparing for da’wa even though the moral state of his people at that time, the Arabs of Mecca was in dire need of guidance. This paper talks about several pre-prophethood events as narrated by many Muslim historians. Through historical approach and inductive reasoning, such events are analysed to reveal their relation with dakwah of the prophet. Findings in this paper reveal that the life of the prophet Muhammad before he became prophet constituted vital role for the dakwah he undertook later on. Prophet’s dakwah also focused more on issues of hereafter and less on issues of halal and haram. Keywords: Arabs, Da’wa, Pre-prophethood